On the pseudoterrestris species group of the spider genus Coelotes (Araneae, Amaurobiidae) - Wang, Xin-Ping; Griswold, Charles E.; Ubick, Darrell (Zootaxa, 2009)
Nine species of the spider genus Coelotes are described from China and Thailand, and assigned to the pseudoterrestris species group. Six of the species are described from both sexes (Coelotes acicularis sp. nov., C. guangxian Zhang et al. 2003, C. pseudoterrestris Schenkel 1963, C. pseudoyunnanensis sp. nov., C. suthepicus Dankittipakul, Chami-Kranon & Wang 2005 and C. thailandensis Dankittipakul & Wang 2003) and three from the female only (C. pseudoguangxian sp. nov., C. yunnanensis Schenkel 1963 and C. yanhengmei sp. nov.). Significant morphological variation in the epigynum and vulva was found in C. pseudoterrestris, a species widespread from eastern to western Yunnan. The combination of significant genitalic variation and widespread occurrence suggest that C. pseuduterrestris may be a cryptic species complexs, but this hypothesis needs to be justified by further collection of both male and female specimens from other localities.